Preliminary Selection on Yield of Three Way Cross QPM Hybrids in West Java-Indonesia - D. Ruswandi; Dwi Wirawan; S. Ruswandi; F. Kasim; M. Rachmadi (Zuriat, 2007)
Thirty-two TWC QPM hybrids were selected based on genotype × environment (G × E) interaction and stability. The experiment was conducted in three locations with differing conditions. TWC QPM hybrids were tested under nitrogen deficient and nitrogen sufficient fertilization at the Padjadjaran University Faculty of Agriculture Experimental Station, Jatinangor, Sumedang from March until July 2004. Another set of TWC QPM hybrids was tested under sufficient nitrogen fertilization at a high altitude location in Pangalengan from June until October 2004. Each experiment was arranged in a randomized block design with two replications with 32 TWC QPM hybrids and two check cultivars, i.e. Bisi-2 and Pioneer-7. Bartlett’s homogeneity test was applied to error derived from analyses of variances of every location. Combined analysis was done since error was homogenous for all observed characters. The combined analysis showed that there was G × E interaction for seed weight per 10 plants. Preliminary METs in West Java successfully selected newly developed TWC QPM hybrids based on stability and interaction between G × E. These hybrids are QPDMR-8-BCP1 and QPDMR-8-BCP2 for wide adaptive cultivars and QPDMR-35-BCP1, QPDMR-26-BCP1, QPDMR-8-BCP1, QPDMR-1-BCP2, QPDMR-8-BCP2, QPDMR-10-BCP2 and QPDMR-15-BCP2 specific adaptive cultivars.